Structural and Thermal Analysis of Fuel Rod of VVER-1200 Nuclear Reactor Using ANSYS Software - Shanta, Shah Nusrat Jahan; Mollah , Abdus Sattar (MIST International Journal of Science and Technology, 2025)
This study focuses on analyzing the thermo-mechanical behavior of fuel rods in VVER-1200 nuclear reactors to ensure their safe and efficient operation. Bangladesh plans to operate two VVER-1200 reactors at Rooppur by 2025/2026, aligning with global efforts to shift toward low-carbon energy sources. The analysis, performed using ANSYS software, evaluates key parameters such as deformation, stress, strain, temperature distribution, and heat flux. A detailed geometric model of the UO₂ fuel rod with zirconium alloy cladding and helium gas in the gap has been developed. Thermal distribution simulations under steady-state conditions reveal critical temperature gradients, while structural analysis identifies high-stress regions due to thermal expansion and operational loads. MIJST, Vol. 13, June 2025 : 65-71 DOI: https://doi.org/10.47981/j.mijst.13(01)2025.510(65-71)